Dramatisasi Abnormalitas Melalui Komposisi Visual Pada Video Musik “Birds of A Feather” - Sanjaya, William (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
Visual composition is one of cinematography elements that functions as an impression through an image. "Birds of A Feather" is a music video that has the application of visual composition in building the impression of abnormality in all its scenes, thus helping to convey the message of the song. This study focuses on the discussion of the application of visual composition in building the impression of abnormality in the scenes in the music video "Birds of A Feather". This study uses a qualitative method with a purposive sampling approach. The theory used is cinematographic composition theory proposed by Gustavo Mercado, namely the rule of thirds with narrow looking room and visual imbalance. It is concluded that there is an application of visual composition in the form of the rule of thirds with narrow looking room and visual imbalance that dominates the frame, thus showing the impression of abnormality in the scene. The impression of abnormality is shown in the incident when Billie sings with a smile and calmness in the midst of an unfavorable situation. Billie is attracted by the force that makes her fall and be pushed.